Paesaggi agrari. L'irrinunciabile eredità scientifica di Emilio Sereni a cura di Massimo Quaini (2011), cinquanta anni dopo Storia del paesaggio agrario - Gabriella Bonini (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The book - catalog Paesaggi agrari. L'irrinunciabile eredità scientifica di Emilio Sereni edith by Massimo Quaini in collaboration with Gabriella Bonini, Claudio Cerreti, Luisa Rossi and Chiara Visentin - acknowledges and deepens into ten chapters the ten sessions in which the documentary exhibition, that brings the same name, is structured and displayed in a permanent space in the Library Archive Institute Cervi in Gattatico (Reggio Emilia). In the process of critical interpretation, embedding documents and images, the book illustrates the path of life, thought and method of Emilio Sereni, fifty years later the publication of Storia del paesaggio agrario italiano (Laterza 1961).